2023
DOI: 10.3390/ijms241512268
|View full text |Cite
|
Sign up to set email alerts
|

Migraine Treatment: Towards New Pharmacological Targets

Marcello Silvestro,
Luigi Francesco Iannone,
Ilaria Orologio
et al.

Abstract: Migraine is a debilitating neurological condition affecting millions of people worldwide. Until a few years ago, preventive migraine treatments were based on molecules with pleiotropic targets, developed for other indications, and discovered by serendipity to be effective in migraine prevention, although often burdened by tolerability issues leading to low adherence. However, the progresses in unravelling the migraine pathophysiology allowed identifying novel putative targets as calcitonin gene-related peptide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 198 publications
(231 reference statements)
0
10
0
Order By: Relevance
“…Advances in preclinical and human models that allow careful control and monitoring of various end points in experimentally induced migraine and associated changes with treatments are providing evidence for other signaling pathways involved in migraine neurobiology. 25 In addition to CGRP, nitric oxide, pituitary adenylate cyclaseactivating polypeptide, and vasoactive intestinal peptide have been observed to induce migraine-like attacks in humans. 25 A recent study in a human provocation model has demonstrated that increasing cAMP with cilostazol during CGRP blockade can induce a migraine attack through CGRP-independent pathways.…”
Section: Current and Future Clinical Developments In Migrainementioning
confidence: 99%
See 1 more Smart Citation
“…Advances in preclinical and human models that allow careful control and monitoring of various end points in experimentally induced migraine and associated changes with treatments are providing evidence for other signaling pathways involved in migraine neurobiology. 25 In addition to CGRP, nitric oxide, pituitary adenylate cyclaseactivating polypeptide, and vasoactive intestinal peptide have been observed to induce migraine-like attacks in humans. 25 A recent study in a human provocation model has demonstrated that increasing cAMP with cilostazol during CGRP blockade can induce a migraine attack through CGRP-independent pathways.…”
Section: Current and Future Clinical Developments In Migrainementioning
confidence: 99%
“…25 In addition to CGRP, nitric oxide, pituitary adenylate cyclaseactivating polypeptide, and vasoactive intestinal peptide have been observed to induce migraine-like attacks in humans. 25 A recent study in a human provocation model has demonstrated that increasing cAMP with cilostazol during CGRP blockade can induce a migraine attack through CGRP-independent pathways. 26 Thus, although CGRP-targeted therapies have significantly advanced migraine treatment, patients with migraine requiring newer therapeutic modalities still exist, suggesting the need for a better understanding of the disease to explore additional mechanisms for intervention.…”
Section: Current and Future Clinical Developments In Migrainementioning
confidence: 99%
“…The etiology of migraines is believed to be multifactorial, involving a combination of genetic predisposition and environmental factors. Neurovascular reactions, triggered by cyclic changes in the central nervous system or specific triggers, contribute to the development of migraines [ 281 ]. While some individuals may experience only isolated episodes, a genetic threshold likely plays a role in the tendency for recurrent attacks [ 280 ].…”
Section: Neurological Disorders and Cannabis Studiesmentioning
confidence: 99%
“…VIP has also been implicated in the pathophysiology of migraine [111]. The similarities between PACAP and VIP in their roles in migraine include: PACAP and VIP are released in conjunction with migraine and cluster headache attacks [112]; PACAP and VIP are potent vasodilators and can cause migraine-like attacks when infused into people [113]; A 2-hour infusion of VIP caused migraine attacks, indicating that VIP plays a significant role in the pathophysiology of migraines and intravenous administration of PACAP-38 caused headaches in all healthy subjects and migraine-like attacks in 58% of patients with a history of migraine without aura [15,35]; PACAP and VIP receptors are preferentially coupled to Gαs, leading to activation of AC, subsequent cAMP production, and activation of PKA [114]; PKA may in turn activate ERKs [115]; PACAP and VIP receptor-mediated signaling pathways are shown to share activities, including vasodilation, neurogenic inflammation, and nociception in rodents [116] ; PACAP and VIP receptors provide a rich set of targets to complement and augment the current CGRP-based migraine therapeutics; VPAC1 receptors play a dominant role in PACAP-induced vasorelaxation in female mice [117].…”
Section: Role Of Pacap In Migrainementioning
confidence: 99%